Effect of Seed Pre-Treatment and Time of Sowing on Germination and Biomass of Cassia angustifolia Vahl. in Arid Regions - Mishra, D K; Bohra, N K (Annals of Arid Zone, 2016)
Studies have been conducted to develop seed germination and suitable agri-silvi practices for Cassia angustifolia in arid areas under rainfed and irrigated conditions. Seeds were found dormant due to physical reasons and gave poor germination without any pre-treatment. The germination can be enhanced (>80%) by mechanical scarification, hot water and acid pre-treatments. Green seeds in the lot showed slightly poor germination as compared to yellow seeds. Seeds of tested seedlots without treatment gave 22% to 41% germination and average mean germination time was from 4.1 to 5.1 days. However, pre-treatments enhanced the germination percentage and reduced the mean germination time in almost all the lots. Various experiments were initiated with different spacing (30 x 30 cm, 30 x 45 cm and 45 x 45 cm), date of sowing (July, August and September) and irrigation trials. In another experiment various agroforestry tree species namely Acacia nilotica, Prosopis cineraria, Azadirachta indica and Eucalyptus camaldulensis have been selected for experimental trial with a single frequency of irrigation (after 1st plucking) in 3 replication and RBD design.